Behandling av hanhundar med deslorelin - Jigler, Emilia (2009)
This article presents a survey of male dogs treated with the gonadotropin releasing hormone (GnRH) agonist deslorelin (Suprelorin®, Virbac) at three animal clinics in central Sweden. Filled-in questionnaires from 110 dogs were received. The paper also includes a review of existing litterature concerning reproduction in male dogs, focusing on endocrinology, the effects of gonadectomy and the GnRH agonist deslorelin.